Evaluation of Miller cycle and fuel injection direction strategies for low NOx emission in marine two-stroke engine. (3rd August 2017) - Zhou, Song; Gao, Ruifeng; Feng, Yongming; Zhu, Yuanqing
Abstract: A full cycle computational fluid dynamics (CFD) simulation model has been established to study the effect of injection direction and exhaust valve close (EVC) timing on performance and emissions for a slow speed marine engine. In order to find more combustion details, the model was coupled with simplified chemical kinetics mechanism. Meanwhile the paper presents the optimization results combining variable injection direction with late exhaust valve closing (LEVC). The results indicate that the consistency of injection direction and flow direction has an important impact on fuel economy. To improve fuel consumption, the injection direction must be carefully adjusted within certain limits. A certain degree of sacrifice in fuel economy is reflected on the transient calculation using the LEVC strategy. However, significant improvement in NOx (nitrogen oxides) emission can be achieved accordingly. With optimized EVC timing and injection direction, lower NOx emission can be realized with no penalty of fuel consumption. Highlights: Application of CFD on large-scale dimension of marine engine. Oxygen content has a greater effect on NOx emission. New arrangement of injection direction improves fuel consumption. NOx decreases 13% without penalty of fuel consumption.